First evidence of schmallenberg virus infection in southern Italy - Gianmarco Ferrara; Kerstin Wernike; Giuseppe Iovane; Ugo Pagnini; Serena Montagnaro (BMC Veterinary Research, 2023)
Abstract Background Schmallenberg virus (SBV) is a vector-borne pathogen that mainly affects ruminants. Schmallenberg disease has never been described in southern Italy, although this geographic area displays climatic features suitable for Culicoides biting midges, which transmit the pathogen. An observational study was carried out in the Campania region in 2020 to evaluate the seroprevalence in cattle and water buffalo as well as to identify the risk factors involved in the distribution of SBV. Results Relatively high seroprevalences of 38.2% (cattle) and 43% (water buffalo) were found by using a commercial SBV ELISA, which is comparable to the prevalence obtained in other countries under post-epidemic conditions. A virus neutralization assay performed on positive samples showed high titers in a large percentage of animals which is assumed to indicate recent exposure. Bivariate analysis of several variables revealed some environmental factors associated with higher seroprevalence, such as mean annual temperature, distance from the coast, and altitude. Multivariate logistic regression confirmed the statistical association only for mean annual temperature, that was found to be the main factor responsible for the distribution of the virus in southern Italy. In addition, molecular diagnosis attempts were performed on serum samples and resulted in the detection of SBV RNA in two herds and six animals. Conclusions In this work we have demonstrated the circulation of SBV in southern Italy using both molecular and serological assays. This study emphasized the essential role of monitoring in preventing the re-emergence of vector-borne diseases in ruminants.